STRATEGIC COMMUNICATION FOR CULTURAL IMAGE BUILDING THROUGH INSTAGRAM: A CASE STUDY OF @SANGGAR_SENISETIYANEGARA AND THE CIREBON MASK DANCE - Umi Umayah; Melani Rosmayanti Fazrin; Farida Nurfalah (CV. RADJA PUBLIKA, 2025)
The Cirebon Mask Dance (Tari Topeng Cirebon) is a traditional Indonesian art form with deep historical and philosophical values. This study examines how Instagram is utilized as a communication tool to build a positive public image of the dance, focusing on the account @sanggar_senisetiyanegara. The research adopts a qualitative descriptive approach, collecting data through interviews, documentation, and literature review. Data were validated using source triangulation and analyzed through data reduction, display, and conclusion drawing. Guided by the strategic communication framework developed by Halland, Holtzhausen, Van Ruler, Vercic, and Sriramesh (2007), this study identifies three key dimensions of communication strategy: message planning, media selection, and delivery technique. The findings show that Instagram features such as Reels, Stories, and Carousel Posts are effective in fostering engagement and cultural appreciation. However, challenges persist in the form of inconsistent content production, low digital literacy among art practitioners, and limited audience reach. To address these issues, the study highlights the use of educational storytelling, audience interaction, and collaboration with cultural communities as crucial strategic responses. Overall, this research underscores the importance of culturally sensitive and visually compelling communication in promoting traditional arts in the digital era.